Comparison of Three Phenotypic Methods for Detection of Extended-Spectrum β-Lactamase (ESBL) Producing Klebsiella Pneumoniae - Jumaah Dakel Hussein (Journal of Global Pharma Technology, 2017)
Through a period extended from October to December, 2016. Fifty six of Klebsiella pneumonia isolates were collected from some hospitals in Baghdad. The isolates of K. pneumonia were obtained from various clinical specimens including: 39(69.65%) isolates from blood, 6(10.71%) isolates from urine,6(10.71%) isolate from burns, 3(5.36%) isolate from sputum and 2(3.57%) isolates from ear swabs. Our result shows a high level resistance of K. pneumonia clinical isolates towards most of the antibiotics under test, all K. pneumonia isolates had the highest resistance rate 100% to Ampicillin followed by (87.6%) to Cefazolin, while the lowest level resistance of K. pneumonia isolates was to Imipenem which had 17.86% resistance rate. Three methods were used for phenotypic detection of ESβL producing Klebsiella pneumoniae, first one was done by Vitek-2 system and the results showed that out of 56 isolates, 45 (80.35%) isolates were gave positive results for ESβL producing while 11(19. 65%) isolates of K. pneumonie were gave negative results. While in second method (disc combination method) the results showed that out of the 56 K. pneumonia isolates, 48(80.35%) isolates were positive ESβL producing, while 8(19. 65%) isolates of K. pneumonie were negative by two sets of cartridges (D52C) discs. In the third method the results of CHRO Magar technique, 51(91.07%) of the 56 isolates gave positive result which suspected ESBL producers while only 5(8.93%) isolates gave negative result. Eventually, CHRO Magar technique was recorded a high percent of ESBL detection while method by using Vitek-2 system was recorded a low percent of ESBL detection. From study we noticed that a high percent of ESBL producing K. pneumoniae isolates compared with non ESBL producing K. pneumoniae isolates under test by all previous confirmatory methods used in this study.Keywords: Klebsiella pneumoniae, Extended-Spectrum β-Lactamases (ESBL), phenotypic detection